The experience of providing of early care for children with ASD and children in the group of ASD symptoms risk in the Center for Medical Pedagogics and Differential Education of Pskov Region - Nazarkina S.I (Moscow State University of Psychology and Education, 2017)
Department of early help of the Center for Medical Pedagogics and Differential Education of Pskov re¬gion is the primary branch in the system of complex help to a special child and support to their family. The paper describes the conditions of providing effective support to children with high risk of forming ASD, stages of early help to children with ASD and their families. An example of work with an early age child is described.